(untitled) (REM. Chilean Journal of Musical Education, 2025)
In this paper, we discuss the initial findings of a 7-day community-immersive learning experience in which a cohort of music education students of the University of Veracruz had the opportunity to learn the way in which local Huasteco music culture bearers are transmitting their musics traditions to children and youth. We provide findings from a focus group that took place during the last day of the communityimmersive learning experience. In this focus group, the music education students, a community-led organization member representative, a research assistant, a music professor/researcher, and a researcher.